Troubled Financing Handling Efforts at PT. Bank Sumut Syariah Medan Branch Katamso - Lisnawati Lisnawati; Sugianto Sugianto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The Bank of North Sumatra has undergone significant developments, but this must be balanced with regulations and good banking management. Non-performing financing is financing that often occurs due to factors that hinder the growth rate of operational activities. One of the external factors that causes problematic financing at this time is the Covid-19 pandemic. Non-performing financing at the SUMUT sharia bank will reduce or decrease the bank's income. Therefore, the Bank SUMUT Medan Katamso Branch uses a strategy in overcoming non-performing financing so that existing financing will continue to increase every year. The purpose of this study is to determine the procedures for handling problematic financing at Bank SUMUT Medan Katamso Branch and to find out what factors cause problematic financing.